The Frighteners cd.2 - Jackson, Peter; Busey, Jake.; Jeffrey CombsDee WallaceStone; John Astin; Peter Dobson; Trini Alvarado; Michael J Fox (USA Universal Pictures, 1996)
A psychic private detective who consorts with deceased souls becomes engaged in a mystery as members of the town community begin dying mysteriously. While investigating, he is aided by a friendly doctor who believes in his psychic abilities and is hindered by a crazed G-Man, a woman involved in an old serial killing, and what may be the spirit of Death itself.
A psychic private detective who consorts with deceased souls becomes engaged in a mystery as members of the town community begin dying mysteriously...
Fran Walsh
Languages: English Subtitles: English, Dutch, French, German, Italian, Portuguese, Spanish, Danish, Finnish, Norwegian, Swedish
Keywords: Fantasy; Horror; Thriller -- Tv Series; Comedy